2020
DOI: 10.1111/luts.12363
|View full text |Cite
|
Sign up to set email alerts
|

Is there a unique symptom in lower urinary tract dysfunction in children?

Abstract: Objectives Lower urinary tract symptoms (LUTS), particularly urgency, incontinence and intermittency are common in children and it is suggested that the specific symptoms may be used for definite diagnosis for LUT dysfunction (LUTD). This study was performed to investigate the relationship between each LUTD and its associated symptoms, using uroflowmetry/electromyography (UF/EMG) as a diagnostic tool. Methods Each patient was categorized into one of four LUT conditions which were overactive bladder (OAB), dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the present study, there were no significant differences noted in the total DVSS scores and voiding dysfunction diagnoses when the children's bell‐shaped uroflow curves were compared to those with nonbell‐shaped uroflow curves. Özen et al reported weak correlations between symptom specificity, symptom clusters, and lower urinary tract dysfunction 24 . Thus, a symptoms‐based approach may lead to misdiagnoses in cases of lower urinary tract dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there were no significant differences noted in the total DVSS scores and voiding dysfunction diagnoses when the children's bell‐shaped uroflow curves were compared to those with nonbell‐shaped uroflow curves. Özen et al reported weak correlations between symptom specificity, symptom clusters, and lower urinary tract dysfunction 24 . Thus, a symptoms‐based approach may lead to misdiagnoses in cases of lower urinary tract dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Özen et al reported weak correlations between symptom specificity, symptom clusters, and lower urinary tract dysfunction. 24 Thus, a symptoms-based approach may lead to misdiagnoses in cases of lower urinary tract dysfunction. Lower urinary tract dysfunction is associated with urinary tract infections, vesicoureteral reflux, renal scarring, and psychological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to modernized lifestyle, the prevalence of LUTS in children increases because of inappropriate voiding habits and toilet training [ 4 , 5 ]. Epidemiologically, the ratio of LUTS in school-aged children is around 2 to 20 percent, mostly urgency, intermittency, urinary incontinence and enuresis, which affect social limiting and decrease health related quality of life of the children and the parents [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%